2021
DOI: 10.3390/cancers13236148
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Quality Control and Quality Assurance (QC/QA) Program Significantly Improves Inter-Laboratory Concordance Rates of Flow-Cytometric Minimal Residual Disease Assessment in Acute Lymphoblastic Leukemia: An I-BFM-FLOW-Network Report

Abstract: Monitoring of minimal residual disease (MRD) by flow cytometry (FCM) is a powerful prognostic tool for predicting outcomes in acute lymphoblastic leukemia (ALL). To apply FCM-MRD in large, collaborative trials, dedicated laboratory staff must be educated to concordantly high levels of expertise and their performance quality should be continuously monitored. We sought to install a unique and comprehensive training and quality control (QC) program involving a large number of reference laboratories within the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…The performance of some laboratories was variable during the study, reflecting non-strict adherence to SOPs over time (Figure S7) and indicating the need for continuous quality assessment, complemented by educational programmes on the standardization of methods even for experienced laboratories, as previously demonstrated. 12,13 Our results showed that standardization resulted in a greater accuracy in the MRD evaluation of BCP-ALL in different laboratories and on different MFC platforms, as previously described, 14 and also that MFC reproducibility is possible in a multicentre study if the laboratories adhere to the proposed SOPs. Comparability between samples will also be essential to enable automated analysis using the EuroFlow database.…”
Section: Multicentric Standardization Of Minimal/measurable Residual ...supporting
confidence: 73%
“…The performance of some laboratories was variable during the study, reflecting non-strict adherence to SOPs over time (Figure S7) and indicating the need for continuous quality assessment, complemented by educational programmes on the standardization of methods even for experienced laboratories, as previously demonstrated. 12,13 Our results showed that standardization resulted in a greater accuracy in the MRD evaluation of BCP-ALL in different laboratories and on different MFC platforms, as previously described, 14 and also that MFC reproducibility is possible in a multicentre study if the laboratories adhere to the proposed SOPs. Comparability between samples will also be essential to enable automated analysis using the EuroFlow database.…”
Section: Multicentric Standardization Of Minimal/measurable Residual ...supporting
confidence: 73%
“…MFC-MRD detection was performed with an 11-color panel (10 antibodies and DNA-stain Syto41, Thermo Fisher Scientific, Waltham, MA, USA) generally, according to the I-BFM-FLOW network guidelines [ 26 ], but with an adjustment for possible CD19 loss. Bone marrow aspirates were stained according to the manufacturer’s instructions, with appropriate amounts of directly conjugated monoclonal antibodies (MoABs) used for the sample cellularity.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphoblasts were considered leukemic if they represented a distinct population with leukemia-associated phenotypes and lymphoid light-scatter parameters. As per the I-BFM-FLOW network guidelines [ 26 ] and in accordance with the EuroFlow standardized approach [ 28 ], we defined a minimum of ten clustered leukemic lymphoblasts to consider a sample as MRD positive (lower limit of detection—LOD). The proportion of the leukemic cell population was presented as the percentage of Syto41-positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…MRD was assessed by MFC in three laboratories (two in Russia and one in Belarus) according to well-harmonized approach [40] based on AIEOP-BFM-ALL-MRD-Flow study group guidelines [42], as previously described [40]. All three laboratories use the MFC methodology based on standard analyses, and had participated in AIEOP-BFM QA [43] system as well as in intragroup proficiency tests [40]. 4-9-color MFC was used to evaluate the expression of antigens commonly used for MRD detection in BCP-ALL: CD19, CD10, CD34, CD45, CD20, CD38, CD58, and CD11a [40].…”
Section: Mrd Investigationmentioning
confidence: 99%